2018
DOI: 10.3390/su10030583
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Integrated Approach to Environmental and Prosocial Education

Abstract: Environmental education programs neglect the aspect of prosocial behavior as a correlate of pro-environmental behavior. This article examines the possible benefits of increasing the emphasis on prosocial behavior as a way to reinforce environmental education. In our study, prosocial behavior was positively related to pro-environmental behavior (r = 0.34, p < 0.001), and even a combined scale consisting of prosocial and pro-environmental behavior items showed an acceptable reliability (separation reliability = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 44 publications
2
51
0
3
Order By: Relevance
“…Environmental values and behaviours-plus nature relatedness-have been identified as being strongly linked in a number of studies [2,14,16,17,55,64,156], with the latter being the best predictor of ecologically conscious behaviour [65]. Pro-environmental behaviour has been found to be strongly linked to prosocial behaviour, with an increase in one fostering an increase in the other through their mutually enhancing interrelationship [157]. However, it is possible to conceive how self-identification with nature may on the other hand potentially also increase depression, anxiety or stress as a result of increased environmental concern and awareness of local and global ecological degradation [58].…”
Section: Psychedelic-assisted Nature Exposure For Fostering Greater Ementioning
confidence: 99%
“…Environmental values and behaviours-plus nature relatedness-have been identified as being strongly linked in a number of studies [2,14,16,17,55,64,156], with the latter being the best predictor of ecologically conscious behaviour [65]. Pro-environmental behaviour has been found to be strongly linked to prosocial behaviour, with an increase in one fostering an increase in the other through their mutually enhancing interrelationship [157]. However, it is possible to conceive how self-identification with nature may on the other hand potentially also increase depression, anxiety or stress as a result of increased environmental concern and awareness of local and global ecological degradation [58].…”
Section: Psychedelic-assisted Nature Exposure For Fostering Greater Ementioning
confidence: 99%
“…Recently, studies have revealed that altruism or altruistic motivation has a significant effect on increasing the individual's environmental awareness level when a simple Likert scale is used to measure environmental awareness [5][6][7]. Furthermore, many studies use Likert-type scales to evaluate an individual's environmental awareness level [8][9][10], but these studies do not test or mention whether a simple Likert-type environmental awareness index can capture altruism as measured by a psychometric altruism index: an index used in psychology to identify an individual's altruism level through compounding various items reflecting an individual's altruistic actions.…”
Section: Introductionmentioning
confidence: 99%
“…The study of prosocial behavior has emerged as a crucial issue across many diverse disciplines in social and behavioral sciences to advance towards an inclusive and sustainable society [1]. Developing inclusive, innovative and reflective societies is at the heart of the current European agenda for a sustainable development [2].…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, schools can be an optimal context for implementing effective interventions that support positive relationships and interactions to ultimately provide students' social, academic and emotional development. Therefore, gathering scientific evidence on which interactive learning environments are effective to foster prosocial behavior, might be a relevant contribution for advancing towards inclusive and sustainable societies [1]. This paper aims at analyzing the efficacy of two particular interactive learning interventions, namely Dialogic Literary Gatherings and Interactive Groups, to improve prosocial development among elementary students.…”
Section: Introductionmentioning
confidence: 99%